2021
DOI: 10.1038/s41598-021-91110-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and efficacy of maximum fluorescein tear break-up time in diagnosing dry eye disease

Abstract: This study aims to investigate the reliability and efficacy of maximum fluorescein tear break-up time (FTBUTmax) in diagnosing dry eye disease (DED). 147 participants were enrolled in this study. Ocular symptoms were assessed by Ocular Surface Disease Index (OSDI). The fluorescein tear break-up time (FTBUT) examination, corneal fluorescein staining (CFS), and Schirmer I test were performed on both eyes. Each participant underwent 3 consecutive FTBUT tests, and five types of FTBUT values including FTBUTmax, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…First, in terms of the interobserver reliability of TFBUT, Mou et al reported that the reliability of the TFBUT in AUC was 0.695–0.792, and the correlation coefficient was 0.244–0.556 among the 147 DED and non-DED participants 37 . Moreover, Paugh et al demonstrated an AUC of 0.917, sensitivity of 0.870, and specificity of 0.810 using the same 2.0 μl of fluorescent solution in 174 cases 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in terms of the interobserver reliability of TFBUT, Mou et al reported that the reliability of the TFBUT in AUC was 0.695–0.792, and the correlation coefficient was 0.244–0.556 among the 147 DED and non-DED participants 37 . Moreover, Paugh et al demonstrated an AUC of 0.917, sensitivity of 0.870, and specificity of 0.810 using the same 2.0 μl of fluorescent solution in 174 cases 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the interobserver reliability of TFBUT, Mou et al reported that the reliability of the TFBUT in AUC was 0.695-0.792, and the correlation coe cient was 0.244-0.556 among the 147 DED and non-DED participants. 37 41 These AI models are not DED diagnostic models and do not provide exact TFBUT estimation. However, these imaging methods applied a similar logic for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…First, for interference imaging of the tear film, the subjects were instructed to keep their eyes open for up to 30 s until tear-film break-up occurred, following a natural blink. After a 30-s recovery, 51 they were asked to look directly at the video camera for 1 min to record the blink pattern. They were then instructed to keep their eyes open for 10 s to measure the ocular surface temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The average value provides a more reliable result ( 104 ). A recent study showed that the maximum TBUT may also be considered to diagnose dry eye ( 105 ). The sensitivity and specificity of the TBUT test are 72 and 61%, respectively.…”
Section: Tear Examinationmentioning
confidence: 99%
“…The sensitivity and specificity of the TBUT test are 72 and 61%, respectively. The diagnostic criteria for fluorescein TBUT in diagnosing dry eye are <10 s ( 105 ). Generally, fluorescein TBUT values can be expected to be shorter than the values of noninvasive TBUT.…”
Section: Tear Examinationmentioning
confidence: 99%